2D and 3D studies of the X-divertor configuration in the future upper divertor of ASDEX upgrade. (May 2019) - Lunt, T.; Pan, O.; Herrmann, A.; Teschke, M.; Dunne, M.; Feng, Y.; Wischmeier, M.; ,
Highlights: Upgrade of the upper divertor for ASDEX Upgrade planned to study alternative divertor configurations. SOLPS predicts an earlier detachment of the XD and LFS SF- configuration. 3D power deposition pattern studied by EMC3-EIRENE for the 'spiral' design shows strong toroidal asymmetries for low density pure deuterium simulations. These are strongly reduced at higher densities and with radiation. 'z-joints' show much smaller toroidal asymmetries even for low-dissipative conditions. Abstract: ASDEX Upgrade is planning the installation of a pair of in-vessel coils in order to study alternative divertor configurations, like an X-divertor (XD) or a Snowflake (SF) in a machine with a high heating power compared to its size. Two designs for the technical realization of these coils are currently proposed, one including z-shaped joints and one with a single spiral conductor. The magnetic fields produced by these conductors intrinsically have a non-axisymmetric component. In particular in the XD configuration, where very shallow field line incidence angles occur, these 3D fields have a strong impact on the power distribution on the outer divertor plate. The 2D and 3D plasma transport is studied by the SOLPS and initial EMC3-EIRENE code simulations, respectively, in order to support the decision making processes of the engineering design. Although several aspects still require further attention, this paper gives a status report. The strong toroidal asymmetries observed in the power deposition pattern for the spiral conductor seem to be strongly reduced, when highly dissipative divertor conditions are reached. The asymmetry for the z-joint design is substantially smaller than the spiral conductor even for low-dissipative conditions.